Serat Wedatama K.G.P.A.A Mangkunegara IV (Kajian Teologi Hindu) - Darma Prasetyo; Relin, D.E.; Poniman (Jurnal Penelitian Agama Hindu, 2019)
It is a pride for the Javanese people in particular as well as the Indonesian people in general, because the previous ancestors inherited many priceless literary works. One of the literary works that is still studied and infused by the Javanese community is Serat Wedatama. Wedatama fiber is a literary work in the form of songs that are classified as didactic moralistic, as stated in Pangkur Pupuh which reads: sinawung resmining kidung, which means: decorated with the beautiful song (tembang). Didactic literary work in Javanese society is a piwulang literature that gives moral guidance which should be carried out by humans. Serat Wedatama is the work of Kanjeng Gusti Pangeran Adipati Arya (K.G.P.A.A) Mangkunegaran IV. The author is interested in examining Hindu Theology in Serat Wedatama K.G.A.A Mangkunegara IV, with problems namely: 1) How is the structure in Serat Wedatama K.G.P.A.A Mangkunegara IV ?. 2) What is the function of Serat Wedatama K.G.A.A Mangkunegara IV ?. 3) What is the meaning of Hindu theology contained in the Fiber Wedatama K.G.A.A Mangkunegara IV ?. This study aims to describe the structure, functions and theology of Hinduism contained in Serat Wedatama K.G.A.A Mangkunegara IV. Accurate data is obtained by using several literature studies, the basis of concepts and theories, namely Talcott Parsons Functional Structural theory and Habermas Hermeneutics theory, and research models. This research method, which starts from the type and approach of research, methods of data collection, literature study, documentation studies, data analysis techniques, and methods of presenting results. Data analysis was performed using descriptive-qualitative analysis techniques. The results of this study indicate that the Serat Wedatama structure consists of five pupuh, namely: Pangkur, Sinom, Pucung, Gambuh and Kinanthi. The number of Serat Wedatama temple is 100 stanzas. The functions obtained in Serat Wedatama are: Art Functions, Social Functions, Cultural Preservation Functions, Religious Functions, and Spiritual Functions. Can be explained that the meaning of Hindu Theology contained in the Fiber Wedatama KGPAA Mangkunegara IV, namely God Almighty (Hyang Tunggal), God All Sources (Hyang Widhi), God Is Everywhere (Hyang Most Holy) and God Who Is Acintya (Hyang Sukma ) which is parallel to the divinity in Siva Tattva. In essence God is the source of everything that exists in the universe and becomes the place for the return of everything. The One God, though still in place, does not move, but His speed exceeds the mind, precedes the speed of movement of the Gods, God is unthinkable, very magical, everywhere, and permeates everything.